Peculiar magnetism in Eu substituted BiFeO3 and its correlation with local structure. (4th October 2018) - Mumtaz, Fiza; Jaffari, G Hassnain; Shah, S Ismat
Abstract: We have systematically investigated the effects of Eu substitution on chemical pressure, bond lengths, microstrain, bond angles, octahedral tilting, vibrational modes and phase transformation, in BiFeO3 . Correlation between concentration, phase, local structure and magnetism has been explained. Substitution of Eu ions with contrasting magnetic moment and dissimilar size, affects the local structure by changing bond angles and hence modifies spin structure through weakening of Dzyaloshinsky–Moriya (DM) interaction which lead to destruction of spiral spin configuration. Intriguing as well as anomalous magnetic response such as weak ferromagnetism with high coercivity, stair step like loops with significant drop in coercivity and systematic decrease in the magnetic coercivity at low temperatures has been observed as a function of Eu concentration ( x ). These results are explained on the basis of weakening of DM interaction, field induced melting of antiferromagnetic clusters and modification in effective magnetic anisotropy including contribution of magnetoelectric coupling, for various values of x . These results were used to generate the magnetic phase diagram.